PERSUASIUNEA: ARTA SAU PUTEREA DE A CONVINGE - USM ADMIN (Studia Universitatis Moldaviae: Stiinte Sociale, 2007)
The persuasion in this article is revealed both: as a persuasive power and as an art. It is a power because the persuaded person joins all the rethorical factors, functions, elements, techniques and laws. The art of influenced person consists in the way she/he cooperates with them having as a result the logical hierarchy of the presented arguments and of the public attitude changes. In this case the attitude represents the way of programming “for” or “against” the received message. The persuasion is a human activity which flows naturally and it is aimed to persuade consciously of the opinions, values and beliefs.